Chemical composition of the leaves of tea bush (Ocimum gratissium L.) - Adeyeye, EI; Oyarekua, MA (Bangladesh Journal of Scientific and Industrial Research, 2015)
Tea bush leaves are important in the preparation of soups. Crude fat was 5.20g/100g. High value results (g/100g): protein (28.9), carbohydrate (36.2), ash (9.40), fibre (14.1); fatty acid (4.16g/100g) with energy value (154kJ/100g). High major minerals were: Ca, Mg, K and P, high trace minerals were: Fe, Cu, Mn and Zn. Mineral ratios within nutritional standards: Na/K, Ca/P and [K/(Ca + Mg)]. In amino acid composition, highest concentrated amino acid was Glu (11.0g/100g), second was Leu (7.65g/100g), total amino acid (87.2g/100g). Essential amino acid (with His) was 42.5g/100g (48.7%). Quality parameters obtained in the results: Leu/Ile (1.59), % Cys/TSAA (42.3), P-PER (2.49) and EAAI (1.18). On quality criteria, Lys was limiting in the three criteria used. Fatty acid had values of SFA (30.9%), MUFA (5.60%), PUFA (63.5%), PUFA/SFA (2.06), n-6/n-3 (1.52), EPA/DHA (1.39). Total phospholipids (44.1mg/100g) with phosphatidylcholine (15.9), phosphatidylinostitol (14.9) predominating. Cholesterol was 0.00mg/100g, sitosterol was 26.3mg/100g (61.5%). Bangladesh J. Sci. Ind. Res. 50(2), 93-108, 2015